CMPK2 promotes NLRP3 inflammasome activation via mtDNA‐STING pathway in house dust mite‐induced allergic rhinitis - YaoMing Zheng; YaDong Xie; JiaYing Li; YuJie Cao; Min Li; Qing Cao; MiaoMiao Han; HongFei Lou; YiLai Shu; Hui Xiao; HuaBin Li (Clinical and Translational Medicine, 2025)
Abstract Background House dust mite (HDM) is the leading allergen for allergic rhinitis (AR). Although allergic sensitisation by inhaled allergens renders susceptible individuals prone to developing AR, the molecular mechanisms driving this process remain incompletely elucidated. Objective This study aimed to elucidate the molecular mechanisms underlying HDM‐induced AR. Methods We examined the expression of cytidine/uridine monophosphate kinase 2 (CMPK2), STING and the NLRP3 inflammasome in both AR patients and mice. Additionally, we investigated the role of CMPK2 and STING in the activation of the NLRP3 inflammasome in AR. Results The expression of CMPK2, STING and the NLRP3 inflammasome was significantly increased in the nasal mucosa of AR patients compared to non‐AR controls. A positive correlation was found between CMPK2 expression and the levels of STING, NLRP3, ASC, CASP1 and IL‐1β. HDM treatment up‐regulated the expression of CMPK2, and CMPK2 overexpression enhanced NLRP3 inflammasome activation in human nasal epithelial cells (HNEPCs). Additionally, mitochondrial reactive oxygen species (mtROS) production following HDM exposure contributed to mitochondrial dysfunction and the release of mitochondrial DNA (mtDNA), which activated the cyclic GMP‐AMP synthase (cGAS)‐STING pathway. Remarkably, depletion of mtDNA or inhibition of STING signalling reduced HDM‐induced NLRP3 inflammasome activation in HNEPCs. In vivo, genetic knockout of CMPK2 or STING alleviated NLRP3 inflammasome activation and ameliorated clinical symptoms of AR in mice. Conclusions Our results suggest that HDM promotes the activation of NLRP3 inflammasome through the up‐regulation of CMPK2 and ensuing mtDNA‐STING signalling pathway, hence revealing additional therapeutic target for AR. Key points Cytidine/uridine monophosphate kinase 2 (CMPK2) expression is up‐regulated in the nasal mucosa of patients and mice with allergic rhinitis (AR). CMPK2 caused NLRP3 inflammasome activation via mitochondrial DNA (mtDNA)‐STING pathway. Blocking CMPK2 or STING signalling significantly reduced the activation of NLRP3 in house dust mite (HDM)‐challenged mice and human nasal epithelial cells (HNEPCs).